Wastewater valorization by pure bacterial cultures to extracellular polymeric substances (EPS) with high emulsifying potential and flocculation activities - Drakou, Efi Maria; Amorim, Catarina L.; Castro, Paula M. L.; Panagiotou, Fostira; Vyrides, Ioannis (My University, 2018)
Nowadays much effort has been devoted for the development of cost-effective and environmentally friendly processes to obtain extracellular polymeric substances (EPS) with high emulsifying and flocculation activities. The aim of this study was to evaluate the capacity of bacterial strains previously isolated from oil-contaminated areas to produce EPS with high emulsification and bioflocculant properties during cultivation in domestic and bilge wastewater and in industrial crude glycerol. A total of seven bacterial strains were screened for EPS production, from which two strains, Pseudomonas aeruginosa LVD-10 and Enterobacter sp. SW, were selected as potential EPS producers. EPS with high emulsifying capacity in olive oil (a maximum of 96.6 and 89.8% for strain SW and LVD-10, respectively) was produced using bilge wastewater as substrate. EPS with a slightly lower emulsifying capacity was obtained using crude glycerol. In addition, the flocculation activity of the EPS extracted from strains LVD-10 and SW grown on crude glycerol was considerably higher (81.6 and 73.3%, respectively) than that obtained with other substrates. This is the first study that points out that EPS with emulsifying and flocculation potential activity can be produced from bilge wastewater and crude glycerol. The production of biopolymers with broad biotechnological applications using low-cost substrates can be a means to valorise waste streams.
Keywords: Biovalorization; Emulsification; Extracellular polymeric substances; Flocculation activity